Between Location Decisions and Decisive Locations: German Reporting from West Asia and North Africa - Rückerl, Lena (Global Media Journal - German Edition, 2024)
The foreign reporting of German media reflects a distinctly unequal view of the world, characterized by significant disparities in the frequency and manner of coverage across different countries and regions. This article examines the relationship between the locations of foreign correspondents of German media and the focus of their reporting, using the West Asia and North Africa (WANA) region as an example. The study employed desk research methods to first map the distribution of all permanently stationed correspondents in WANA by German media. This was followed by an analysis of the reporting from three selected correspondents, focusing on the countries featured in their reports. Findings reveal an uneven distribution of 39 correspondents, with a concentration in a few countries such as Israel and Egypt, while vast areas of the region receive minimal or no coverage. Drawing on news factor theory, the study argues that locations with high conflict density and international significance are prioritized. However, traditional news factors alone do not fully account for the uneven distribution. Logistical and security-related factors also significantly influence coverage decisions. A closer analysis of the reporting demonstrates that correspondents’ locations heavily shape the diversity of topics and geographic focus. Reports predominantly center on the countries where the correspondents are stationed, leading to a narrowed scope of coverage across the broader region.